2021
DOI: 10.1038/s41598-021-03293-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel sequence-based predictor for identifying and characterizing thermophilic proteins using estimated propensity scores of dipeptides

Abstract: Owing to their ability to maintain a thermodynamically stable fold at extremely high temperatures, thermophilic proteins (TTPs) play a critical role in basic research and a variety of applications in the food industry. As a result, the development of computation models for rapidly and accurately identifying novel TTPs from a large number of uncharacterized protein sequences is desirable. In spite of existing computational models that have already been developed for characterizing thermophilic proteins, their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 66 publications
0
52
0
Order By: Relevance
“…This might be due to the fact that LogitBoost were trained using larger samples. For the last independent dataset, it was constructed by Charoenkwan et al (2021[ 11 ]). This dataset was utilized to evaluate the performance of ThermoPred and SCMTPP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be due to the fact that LogitBoost were trained using larger samples. For the last independent dataset, it was constructed by Charoenkwan et al (2021[ 11 ]). This dataset was utilized to evaluate the performance of ThermoPred and SCMTPP.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SCMTPP was applied to determine informative physicochemical properties (PCPs). Charoenkwan et al (2021[ 11 ]) reported that FUKS010101 (R = 0.616), FUKS010101 (R = 0.523) and FUKS010109 (R = 0.307) were considered as the top three informative PCP used for analyzing TPPs and non-TPPs. Charoenkwan et al's analysis showed that the content of hydrophobic amino acids in TPPs was not different from non-TPPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After performing parameter optimization, and λ values of 0.5 and 10, respectively, were used. The parameter optimization in the current study is the same as employed in our previous studies 31 34 .…”
Section: Methodsmentioning
confidence: 99%
“…More detailed information for the SCM classifier construction is provided in our previous studies. 13 15 , 17 , 20 …”
Section: Methodsmentioning
confidence: 99%